Improving Capital Structure through Firm Size and Sales Growth: The mediating role of Managerial Ownership - Nainggolan, Bonifasius MH; ., Surachman; Aisjah, Siti; ., Sumiati (Journal of Ecohumanism, 2024)
Conflict between ownership and management constitutes a significant concern within organizational dynamics. Nevertheless, the alignment of the interests between owners and management can be advanced by promoting managerial ownership. Prior research delving into the role of managerial ownership as an intermediary variable linking firm size and sales growth, with capital structure remains rather limited, particularly in the context of non-financial companies listed on the IDX. This study investigates the correlations between firm size and sales growth with capital structure, mediated by managerial ownership. This investigation focuses on non-financial entities that are not state-owned enterprises and are listed on the IDX. Hypothesis testing in this study was conducted using path analysis. Path analysis is calculated by decomposing the causal influence model between direct and indirect variables. The findings of this study add to a more profound understanding on how firm size, when mediated by managerial ownership, impacts the capital structure, as indicated by the LTDR proxy. This underscores that managerial ownership, as a means of mitigating agency conflicts, can exert an influence on management's decision-making concerning the proportion of long-term debt within the capital structure. It is worth noting that Managerial ownership does not serve as a substantial mediator in the influence of sales growth on the capital structure.